Expression and purification of glyceraldehyde-3-phosphate dehydrogenase from psychrophilic bacterium - Few Ling, Ling (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Organisms that thrive in cold environments are known as psychrophiles. One of the strategies for their cold adaptation is the ability to synthesize cold-adapted enzymes. Our collection of cold-tolerant microorganisms isolated· from the Antarctic region has offered a potential source for psychrophilic enzymes. Previously our group had successfully cloned the open reading frame for GAPDH gene from an Antarctical bacterium known as phi9. The ORF was cloned into a pET-14b plasmid. The full length GAPDH protein was subsequently expressed in E. coli strain BL21 (DE3), purified as His-tag protein and confirmed to be catalytically active. Results showed that IPTG concentration did not have any effect on protein expression and solubility while 3 hours of induction time at room temperature (28°C) was the best conditions for the expression and solubility of this protein. This protein was shown to be most active at 38°C and its specific activity increased by 40% from 3.6 JlmOI/min/mg to 6.1 J.UllOifmin/mg when the temperature increased from 23°C to 38°C. This work laid the foundation for further biochemical and structural characterizations of GAPDH from a psychrophilic bacterium by providing a highly purified recombinant protein sample.